A dual functional bone‐defect‐filling material with sequential antibacterial and osteoinductive properties for infected bone defect repair. Issue 10 (17th June 2019) - Wang, Dongyun; Liu, Yi; Liu, Yuelian; Yan, Liang; Zaat, Sebastian A.J.; Wismeijer, Daniel; Pathak, Janak L.; Wu, Gang
Abstract: Infected bone defect healing is hindered by infection and compromised bone regenerative capacity. In this study, we designed a dual functional bone‐defect‐filling material with a sequential release system, that is, a burst release of a potent antibacterial agent, hydroxypropyltrimethyl ammonium chloride chitosan (HACC), followed by a controlled release of osteoinductive bone morphogenic protein (BMP2) to repair the infected bone defect. Minimum bactericidal concentration (MBC) of HACC against methicillin‐resistant Staphylococcus aureus was 40 μg/mL. HACC at 40 μg/mL did not affect preosteoblast proliferation and did not influence the BMP2‐induced alkaline phosphatase activity, osteocalcin expression, and matrix mineralization. in vitro release profile revealed burst release of HACC followed by a slow release of BMP2. in vivo bone formation was observed only in the BMP2‐containing groups. HACC did not influence of biomimetic calcium phosphate (BioCaP) resorption and BMP2‐induced bone formation. In conclusion, the optimized HACC/BMP2‐incorporated BioCaP complex showed strong antibacterial effect and robustly enhanced osteoinduction both in vitro and in vivo. Abstract :